Effectiveness of the Otago Exercise Program in Reducing Fall Risk Among Community-Dwelling Older Adults in Sidoarjo, Indonesia: A PreExperimental Study - Dwi Miftakhurroiba Rahma; Minarti; Adin Mu'afiro; Sri Utami (International Journal of Advanced Health Science and Technology, 2026)
The aging process is associated with progressive degenerative changes that increase the risk of falls among older adults. Declining physiological functions, including reduced muscle strength, impaired coordination, postural instability, and decreased balance, contribute significantly to fall incidents, which may lead to physical injury, reduced independence, and decreased quality of life. Therefore, effective interventions are needed to minimize fall risk and improve functional mobility in the elderly population. This study aimed to determine the effect of the Otago Exercise Program on fall risk among older adults in Gelang Village, Sidoarjo Regency. This study employed a pre-experimental design using a one-group pretest–posttest approach. A total of 30 older adults were recruited through purposive sampling. The intervention consisted of the Otago Exercise Program administered over 12 sessions within four weeks. Fall risk was assessed using the Timed Up and Go (TUG) test before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test to evaluate differences in fall risk scores between pretest and posttest measurements. The findings demonstrated a statistically significant reduction in fall risk following the intervention. The Wilcoxon test revealed a p-value of 0.000 (p < 0.05), indicating that the Otago Exercise Program effectively improved balance and mobility among the participants. Post-intervention observations showed that participants experienced better functional movement and a lower risk of falling compared to their baseline condition. In conclusion, the Otago Exercise Program has a significant positive effect on reducing fall risk among older adults in Gelang Village, Sidoarjo Regency. These findings suggest that the program can be considered an effective non-pharmacological intervention to enhance balance and prevent falls in the elderly population. Future studies are recommended to include additional variables, such as muscle strength, dynamic balance, and quality of life, to provide more comprehensive findings.